Uji Beberapa Media Air terhadap Pertumbuhan Tunas dan Akar Umbi Gembili (Dioscorea esculenta L.) Asal Serui Papua - Siska Syaranamual; Yaved Muyan; Inna Rumainum; Mei Vora Manori (Fakultas Pertanian, Universitas Timor, 2022)
The richness of genetic resources in Papua Province, with its various potentials, has not been studied and utilized in a sustainable manner in order to reduce and prevent germplasm genetic erosion. Thus, optimal management of germplasm is an inseparable part of efforts to maintain genetic resources in order to sustain genetic resources. One of them is the lesser yam which has high cultural value because it is used in traditional ceremonies and is also used as a wedding dowry and as a complement in traditional ceremonies. This means that the cultivation of lesser yam has been integrated into the life of the Papuan people. This study aims to examine several water media on the growth response of young shoots and roots of gembili plants as a cultivation technique to shorten the dormancy period and produce planting material or gembili seeds from Serui Papua. The study was conducted for two months utilizing the Completely Randomized Design (CRD) method which consisted of two treatments, namely immersion in sterile water/aqua/water and well water, the treatment was repeated three times, thus, six experimental units were obtained. From the observations, it can be concluded that using the cultivation technique of soaking tubers with sterile water or aqua water can shorten the dormancy period and increase planting material or gembili (Dioscorea esculenta L.) seeds from Serui Papua. The results of data analysis prove that the application of water media has a significant effect on the growth of shoots and roots on gembili tubers. The comparison of aqua water treatment and well water showed consistency where aqua water treatment expressed the average number of shoots and number of roots at 4 WAP, more than the average of the two parameters in the well water treatment at 5 WAP. It is recommended for further research using the same treatment and other alternative water growing media by extending the observation time.